The Concept of Social Democracy in the Interwar Lsdp Programming Documents and in the Texts of the Party Leader Steponas Kairys (Parliamentary Studies, 2020)
Social democracy played an important role in the history of Western Europe in the 20th century. In Lithuania, the social democratic movement played an important role in the Lithuanian national liberation movement from the late 19th century to the early 20th century. In interwar Lithuania, during its democratic period (1920–1926), the LSDP was one of the few main parliamentary parties in Lithuania. All this, as well as the occasional motive – in 2019, the 140th anniversary of the birth of Steponas Kairys, the leader and ideologue of the historical Lithuanian Social Democracy, is an important argument for explaining the concept of social democracy in the ideology of the interwar LSDP. That is the object of this article. The aim of the article is to find out and reconstruct how it was answered to the questions ”Who are the Social Democrats?”, ”What is the Social Democratic Party”? in the interwar LSDP programmatic documents and S. Kairys’ texts.After analyzing the LSDP programmatic documents and the texts of the party leader S. Kairys, the following conclusions are available: 1) A look at the texts of S. Kairys, the leader and chief ideologue of the interwar period LSDP as well as a look at the programs of this party of this period clearly confirms the statement that the Lithuanian Social Democrats of that time, as in many other countries, the Social Democrats saw themselves as a working-class party based on a Marxist analysis of the development of society, seeking socialism as a social order; 2) The article reconstructs the interwar LSDP programs and The conception of social democracy in Kairys’s texts is clearly refuted thesys by Soviet communist ideology and historiography, that interwar social democracy abandoned Marxism, that it ”betrayed Marxism”, that it allegedly refused to carry out the socialist order, that it ceased to be a working class party; 3) The reconstructed concept of social democracy in the article also shows that by treating themselves as a Marxist-led and socialist party of the Social Democrats, the social democrats of the time considered the communists of the time “their enemies“, “ideological struggle“ with “one of their most important tasks“. Getting acquainted with the concept of social democracy characteristic of S. Kairys and the historical LSDP allows to state that the Lithuanian Social Democrats of that time can be considered anti-Bolshevik Marxist socialists; 4) With regard to the reconstructed concept of social democracy discussed in the article, the historical conditionality of this concept should be noted.
Keywords: Social Democratic Party; LSDP; Social Democracy; Socialism; Democratic Socialism; Steponas Kairys